Future Prospects of Indian Automobiles with Special Reference to Two-wheeler & Motorcycle Segment - Senthilkumar, S.; Mahadevan, A. (Indian Journal of Marketing, 2010)
As the markets in transitional economies open and grow, major challenges and opportunities arise for multinational firms entering these markets, local firms facing these new competitors, and policymakers seeking to increase their technical know how and distribution channel. The study found that competitive hostility, suppliers' power, and market turbulence did not moderate the market orientation-performance relationship. Appreciate the role of public-private partnerships as a win-win situation for private entities, governments, and individual consumers. Things are surely heating up in the 2-wheeler market. The times are changing for the manufacturers. Competition has intensified in last couple of years. Indian two-wheeler industry came in with better products, its sleek bikes. They have always welcomed change. The winds of change are flowing once again. In recent times, we saw two wheeler manufacturers like HH and Bajaj abandoning the 100 cc segment and going for premium segments. The focus being on the domestic markets and then on exports. These are signs of becoming a developed nation and this will increase the energy needs of the country even more.